"A Maid Came Free": From Sighting to Citing in Tracy Chevalier's Girl with a Pearl Earring. Issue 2 (3rd July 2018) - Uzundemir, Özlem
ABSTRACT: Tracy Chevalier's ekphrastic novel Girl with a Pearl Earring explores the relationship between literature and art, as it narrates Jan Vermeer's paintings from the perspective of the story's narrator, Griet, who works as a maid in the Vermeers's house. In her fictional account, Griet gradually becomes the painter's assistant as well as his model, and subverts the gender issues in ekphrasis; the silent and gazed-upon female image in the eponymous painting gains a voice to critique Vermeer's art. This article will deal with Griet's transformation from a young maid into an art critic with respect to the issues in painting, namely colour, light and realistic representation, as well as the paragone between the viewing subject and the viewed object in ekphrasis.